2022
DOI: 10.3390/ma15217765
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Joint Degradation Due to Hardener-to-Epoxy Ratio Inaccuracy under Varying Curing and Thermal Operating Conditions

Abstract: This paper presents the results of an experimental study of adhesive joint strength with consideration of the inaccuracy of the hardener dosage, in the context of evaluating the degradation of joints when used either at ambient or elevated temperatures. The butt joint strength characteristics were assessed for two types of adhesives—rigid and flexible—and two curing scenarios—with and without heat curing. An excess hardener was shown to be significantly more unfavourable than its deficiency, which can ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Humans have spent thousands of years learning about adhesives. Initially, materials derived from natural sources, such as birch tar, bituminous substances (asphalts) or animal collagen derivatives, were used, but the development of this technique has also been facilitated by the constant advancement of knowledge in the disciplines of chemistry, physics, materials engineering and mechanics [29]. There are already tens of thousands of different adhesive formulations on the market.…”
Section: Adhesive Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans have spent thousands of years learning about adhesives. Initially, materials derived from natural sources, such as birch tar, bituminous substances (asphalts) or animal collagen derivatives, were used, but the development of this technique has also been facilitated by the constant advancement of knowledge in the disciplines of chemistry, physics, materials engineering and mechanics [29]. There are already tens of thousands of different adhesive formulations on the market.…”
Section: Adhesive Bondingmentioning
confidence: 99%
“…There are adhesives for detachable joints, such as light paper adhesives and adhesives that are neutralized by solvents or heat, as well as adhesives for high-strength joints that call for specific stages in the bonding process (surface preparation, the application of the adhesive and the joint curing procedure). Figure 10 illustrates adhesive bonding in a honeycomb structure [29]. Today, a wide range of materials are bonded using this method, including simple building materials, tissues (adhesives used in biomedical engineering) and even the most intricately made honeycomb composites utilized in the aerospace sector.…”
Section: Adhesive Bondingmentioning
confidence: 99%
“…For polymer materials, there are several types of modifications: chemical modifications, physical modifications and physical-chemical modifications. Chemical modifications involve, for example, changing the type and amount of hardener to adjust the curing time, strength, chemical and low/high temperature resistance of the material [18][19][20][21]. In physical modifications of epoxy resins, the most commonly used agents include fillers, stabilizers, plasticizers and thinners.…”
Section: Introductionmentioning
confidence: 99%
“…From the moment the first fluoropolymers were obtained in DuPont's labs (in April 1938), their rapid expansion into almost all industries began. The reason for this was the remarkable properties [17,24,[38][39][40][41][42][43][44] perience in the use of anti-adhesion coatings and toxicological studies have confirmed the complete safety of their use. Therefore, fluoropolymers are successfully used in the pharmaceutical industry and medicine.…”
Section: Introductionmentioning
confidence: 99%